Improving geological and process model integration through TIN to 3D grid conversion. (September 2015) - Watson, Carl; Richardson, Jennifer; Wood, Ben; Jackson, Christopher; Hughes, Andrew
Abstract: The ability to extract properties from 3D geological framework models for use in the construction of conceptual and mathematical models is seen as increasingly important, however, tools and techniques are needed to support such information flows. Developing such methodologies will maximize the opportunity for information use and re-use, this is particularly important as the true value of such assets is not always known when they are first acquired. This paper briefly describes the cultural and technical challenges associated with the application of information derived from 3D geological framework models by hydrogeological process models. We examine how these issues are being addressed and present a tool, SurfGrid, which allows a user to generate 3D grids (voxels) of parameterized data from a series of geological surfaces. The procedures and tools described offer the ability to re-use expensively created assets by providing user friendly techniques that enable multidisciplinary scientists to extrapolate property distributions from geological models. Highlights: We examine a lack of wide spread integration between geological and process models. Examples of previous attempts to transfer subsurface properties are given. A new software tool, SurfGrid, and simple information workflow are described. SurfGrid creates open 3D grids of parameterized data from modeled surfaces. The solution supports integrated environmental modeling initiatives.